Treatment of Class II, div. 1 malocclusions using the combination of Orthodontic and Orthopedic Techniques - Zahir Altuğ; Şebnem Parlar; Verda Kural (Galenos Yayinevi, 1988)
In this article, combined treatment with both orthopedic and orthodontic techniques in Class II, div. 1 malocclusion cases having also dental disorders are being discussed. The skeletal deviations in Class II, div. 1 have been corrected into Class I relationship by the orthopedic appliance of activator and cervical headgear combination systems while the teeth showing crowdings and dislocations have been placed into an ideal arch relation by Edgewise technique. The treatment involves extractions in one of the related cases while in the other no extraction has been made.